They're Natural and Everywhere: How Evaluative Practices Permeate the Organization - Florentine Maier; Julia Brandl (BuR - Business Research, 2008)
How do evaluative practices become natural and ubiquitous in an organization? In this paper we integrate findings from previous empirical work on the adoption of evaluative practices in organizations with insights from institutional theory and social psychology research for advancing the understanding of possible states of evaluative practices within organizations and the processes through which organizations become permeated by evaluative practices. Our conceptual model suggests that once evaluative practices have gained a foothold in an organization, they tend to be applied to an increasing number of organizational problems and become taken for granted.
urn:nbn:de:0009-20-13931
Keywords: 650; evaluative practices; audits; managerial accounting; institutional theory; organizations; diffusion; institutionalization; social psychology; Bewertung; Erfolgsfaktor; Organisationsforschung; Sozialpsychologie; Institutionalismus